Subpopulations of anti-β2glycoprotein I antibodies with different pathogenic potential: fine specificity against the domains of β2glycoprotein I - P.L. Meroni; T. Avcin; A. Lojacono; M. Frassi; M. Nuzzo; W.L. Binder; G.L. Norman; M. Motta; C. Nalli; L. Andreoli; A. Tincani (PAGEPress Publications, 2011)
Objective: Anti-β2glycoprotein I antibodies (a-β2GPI) are a laboratory criterion for the antiphospholipid syndrome (APS) and were demonstrated to be involved in the pathogenesis of APS. However, they can also be detected in asymptomatic subjects. It has been suggested that a-β2GPI against Domain1 (D1) associate with thrombosis, while those recognizing Domain4/5 (D4/5) have been identified in non-thrombotic conditions. We evaluate the specificity of a- β2GPI in different clinical situations. Methods: We studied 39 one-year-old healthy children born to mothers with systemic autoimmune diseases (SAD) (15 (38.4%) were born to mothers who were a-β2GPI positive), 33 children with atopic dermatitis (AD) and 55 patients with APS (50 adults and 5 paediatrics). All subjects were IgG a-β2GPI positive. IgG a-β2GPI were performed by homemade ELISA, while IgG a-β2GPI D1 and D4/5 were tested on research ELISAs containing recombinant β2GPI domains antigens. Results: One-year-old children and AD children displayed preferential reactivity for D4/5; patients with APS recognized preferentially D1. We also found a good correlation between a-β2GPI and D4/5 in one-year-old (r=0.853) and AD children (r=0.879) and between a-β2GPI and D1 in the APS group (r=0.575). No thrombotic events were recorded in both groups of children. Conclusions: A-β2GPI found in non-thrombotic conditions (healthy children born to mothers with SAD and AD children) mostly recognize D4/5, in contrast to the prevalent specificity for D1 in the APS group. The different specificity could at least partially explain the "innocent" profile of a-β2GPI in children.